Evaluating the effects of two different kinesiology taping techniques on shoulder pain and function in patients with hypermobile Ehlers-Danlos syndrome - Tudini, Frank; Levine, David; Healy, Michael; Jordon, Max; Chui, Kevin (Frontiers in Pain Research, 2023)
Background: Ehlers-Danlos Syndrome (EDS) consists of a group of commonly inherited connective tissue disorders. Hypermobile EDS (hEDS) is the most common subtype and is characterized by multi-joint pain. Physical therapy is often utilized to address the pain and functional loss in patients with EDS and sometimes use interventions such as Kinesiology Tape (KT) during treatment. Studies related to the effectiveness of KT in patients with shoulder pain is equivocal and there are a lack of studies specific to an EDS population. Purpose: The purpose of this study was to assess the effects of two different KT techniques on shoulder pain and function in individuals with hEDS and shoulder pain. Methods: Patients diagnosed with hEDS and experiencing shoulder pain were recruited from EDS support groups in the northeast United States. Baseline demographic information was obtained followed by the completion of 4 outcome (PRO) measures: the Upper Extremity Functional Index, QuickDASH, Shoulder Pain and Disability Index, and the Western Ontario Shoulder Instability Index. Current pain level; as well as average and worst pain over the past 24 hours were recorded using the numeric pain rating scale (NPRS). Subjects were randomly assigned to receive either an experimental or control shoulder KT technique. Subjects returned 48 hours later to repeat the NPRS and PRO measures. Results: There was no significant difference between the experimental and control tape groups for any outcome measure. There was a significant improvement from pre-taping to 48-hours post taping for each of the 4 PRO measures with large effect sizes (p<0.001; ƞp2 = .517 - .719). Likewise, average, and worst pain over the last 24 hours significantly improved with large effect sizes (p = 0.005; ƞp2 = .225 and p < 0.001; ƞp2 = .382, respectively). Current NPRS levels significantly improved from pre-tape to immediately post-tape (p = .023, ƞp2 = .131) and was maintained through the 48-hour follow up, although no further improvement was seen. Conclusion: KT is an inexpensive and relatively safe intervention that is easy to apply and can offer temporary improvements in pain and function for patients with EDS and shoulder pain.